2020
DOI: 10.30773/pi.2020.0099
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Depression: Its Prevalence and Influence as a Prognostic Factor: A Systematic Review

Abstract: Objective Depression and obesity are two conditions with great impact over global health. This is mainly due to their high prevalence and the morbidity and mortality associated to both. The main aim of the present systematic review is to study the association between obesity and depression and the prognostic implications derived from it.Methods A literature review was performed in the PUBMED database. 18 articles were found (9 cross-sectional studies, 6 longitudinal studies and 3 clinical trials), which were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 30 publications
4
55
1
Order By: Relevance
“…Our findings were consistent with the results of previous studies indicating that depression was associated with weight 28 and was not associated with waist circumference 40 , 42 . Additionally, our crude model results were linked to those of previous studies suggesting that depression was related to BMI in only women 23 , 46 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our findings were consistent with the results of previous studies indicating that depression was associated with weight 28 and was not associated with waist circumference 40 , 42 . Additionally, our crude model results were linked to those of previous studies suggesting that depression was related to BMI in only women 23 , 46 .…”
Section: Discussionsupporting
confidence: 74%
“…Boutelle et al 22 suggested that obesity was associated with future depressive symptoms in adolescent females, even though obesity was not related to major or clinical depression. Blasco et al 23 found an interconnection between depression and obesity. They mentioned that depression increased the risk for obesity in African American adolescent males, and obesity increased the risk for depression in females based on a systematic review study.…”
Section: Discussionmentioning
confidence: 98%
“…A French study by Chauvet-Gelenier et al, 8 reviewed the relation between depression and obesity across different geographical areas and confirmed significant bidirectional relationships between depression and obesity at a group level. A 2020 review by Blasco etal., 9 investigated the researches on the relation between depression and obesity and demonstrated that there is a link between them but the significance of association could not be established.…”
Section: Resultsmentioning
confidence: 99%
“…We selected the following covariates based on the epidemiological evidence for their association with the risk of depression: body mass index (BMI) [21], smoking status [22], alcohol consumption [23,24], leisure-time physical activity [25], comorbid chronic conditions [26], occupation [4], working hours [27], and sleep duration [28] and engagement in Covid-19 related work [29].…”
Section: Exposure Variable and Covariatesmentioning
confidence: 99%